Piperine: Chemical, biological and nanotechnological applications - Quijia, Christian Rafael [UNESP]; Araujo, Victor Hugo [UNESP]; Chorilli, Marlus [UNESP] (De Gruyter, 2021)
Piperine (PIP) is an alkaloid present in several species of piper, mainly Piper nigrum Linn. and P. longum, among other species. The present article provides a comprehensive review of PIP research in the last years concerning its chemical properties, synthesis, absorption, metabolism, bioavailability and toxicity. The reviewed PIP literature has shown many pharmacological properties, such as antidiabetic, antidiarrheal, antioxidant, antibacterial, and antiparasitic activity of PIP. However, its low solubility and absorption make its application challenging. This review also includes advances in the development of nanosystems containing PIP, including liposomes, micelles, metal nanoparticles, nanofibers, polymeric nanoparticles, and solid-lipid nanoparticles. Finally, we discuss different in vitro and in vivo studies to evaluate the biological activity of this drug, as well as some methods for the synthesis of nanosystems and their physical characteristics.
Keywords: Absorption; Metabolism; Nanosystems; Pharmacological activity